2010
DOI: 10.1089/hum.2009.187
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hepatocellular Carcinoma with Adeno-Associated Virus Encoding Interleukin-15 Superagonist

Abstract: Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide, but effective therapies are still needed. The liver has been identified as an important immune organ and is heavily populated with various lymphocyte subsets known to play important roles in cancer immunosurveillance. We hypothesized that activation of hepatic lymphocytes by interleukin (IL)-15, a cytokine known for its ability to trigger proliferation and activation of natural killer (NK) cells, natural killer T cells, and memory CD8(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 53 publications
3
35
1
Order By: Relevance
“…Conversely, loss of the NKG2D ligand ULBP-1 in HCC cells was associated with shorter recurrence-free survival (34). In mice, injection of a hepatotropic adeno-associated virus that delivered IL15 and its receptor expanded the number of NK cells in the liver and prolonged survival in a liver metastatic murine HCC model, whereas depletion of NK cells eliminated the therapeutic effect (35). These data suggest that NK cells are an important component of the HCC microenvironment and might contribute to the control tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, loss of the NKG2D ligand ULBP-1 in HCC cells was associated with shorter recurrence-free survival (34). In mice, injection of a hepatotropic adeno-associated virus that delivered IL15 and its receptor expanded the number of NK cells in the liver and prolonged survival in a liver metastatic murine HCC model, whereas depletion of NK cells eliminated the therapeutic effect (35). These data suggest that NK cells are an important component of the HCC microenvironment and might contribute to the control tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…IL-15 is an attractive drug candidate because of its selective actions on NK and mCD8 + T cells, both of which mediate anticancer and antiviral immunity (7,9). Several papers have demonstrated the efficacy of IL-15 in experimental models of melanoma, pancreatic cancer, and multiple myeloma (29,34). The recent paper by Conlon et al (19) reported clearance of pulmonary lesions in patients with malignant melanoma that were treated with IL-15.…”
Section: Discussionmentioning
confidence: 99%
“…Recent preclinical studies showed that IL-15 SA is more effective than IL-15 in causing regression of established melanoma and pancreatic cancer in mice (26,27). IL-15/IL-15Ra fusion proteins and IL-15 SA-expressing adenovirus expression systems have also been efficacious in experimental tumor models (28)(29)(30). These promising preclinical studies have generated robust interest in the application of IL-15 SA as an anticancer agent.…”
mentioning
confidence: 99%
“…53 A multicolor flow cytometric analysis and the gating strategy were developed for phenotyping tumor-infiltrating immune cells as shown in Supplementary Figure. S1.…”
Section: Methodsmentioning
confidence: 99%